CalliSpheres® microsphere transarterial chemoembolization combined with 125I brachytherapy for patients with non–small‐cell lung cancer liver metastases - Zhao, Guangsheng; Liu, Song; Liu, Ying; Li, Xiang; Yu, Guangji; Zhang, Yuewei; Bian, Jie; Wu, Jianlin; Zhou, Jun; Gao, Fei (Frontiers in Oncology, 2022)
Objective: Poor prognosis and limited treatments of liver metastases from non–small‐cell lung cancer (NSCLC) after radical surgery is a critical issue. The current study aimed to evaluate the efficacy and safety of CalliSpheres® microspheres transarterial chemoembolization (CSM-TACE) plus 125I brachytherapy in these patients. Methods: A total of 23 patients with liver metastases from NSCLC after radical surgery were included. All patients received CSM-TACE for 1 to 3 times, then 125I brachytherapy was carried out following the last CSM-TACE. Complete response (CR), objective response rate (ORR), disease control rate (DCR), survival and adverse events were evaluated. Results: CR, ORR and DCR were 43.5%, 87.0% and 100%, respectively at 3rd month; besides, they were 78.3%, 100% and 100%, accordingly at 6th month. Moreover, most QLQ-C30 subscales of functions (including physical and emotional function) and symptoms (including pain, nausea and vomiting) were generally improved at 3rd month (all P<0.05). Furthermore, median progression-free survival (PFS) was 14.0 (95% confidence interval (CI): 10.4-17.6) months with 1-year PFS rate of 62.9%, but 2-year PFS rate was not reached; besides, median overall survival (OS) was 22.0 (95% CI: 16.8-27.2) months with 1-year OS rate of 91.3% and 2-year OS rate of 43.5%. Additionally, main adverse events included fever (100%), pain (65.2%), liver function impairment (65.2%), fatigue (56.5%), nausea and vomiting (52.2%), which were all categorized as grade 1-2. Conclusion: CSM-TACE plus 125I brachytherapy is effective and safe in patients with liver metastases from NSCLC after radical surgery, providing a potentially optimal option in these patients.